Reflections on the meaning of “memory” - Cárdenas, Uriel A
This paper makes a journey through memory as a concept and as an important figure in the reconstruction of the meaning of the SENA for Colombia. In this way, the reflection makes it possible to examine the SENA’s present and future from its meaning as a collective reference, which is also an individual reference in action, related to the work of formation